A Study of Deixis in the Interview between Barack Obama and Chuck Todd in Meet the President (NOBEL: Journal of Literature and Language Teaching, 2016)
The research investigates the types of deixis, the types of reference and the reference meaning used by Barack Obama and Chuck Todd in Meet the Press interview. In analyzing the data, the researcher uses descriptive qualitative method. The results of the research show that from the total of 372 deixis from 84 conversation, all the five types of Levinson's (1983) deixis can be found. Regarding the references, President Barack Obama contains both anaphora and cataphora.